Sustainable Fisheries Development Policy (Case Study: Wakatobi District, Southeast Sulawesi Province And Morotai Island District, North Maluku Province - Lukman Adam (Jurnal Perikanan dan Kelautan, 2012)
Development of fisheries, including aquaculture sub-sector and capture fisheries in Wakatobi and Morotai Island district concerning the balance between social, economic, and environmental. Fisheries management system includes the development of fisheries attention both aspects. Condition of fishery resources has decreased need fisheries management in order to remain sustainable and deliver sustainable results. Management of fisheries resources should be done in a holistic manner. Strategies in the management of sustainable fisheries resources are: The integration between environmental, economic and social alignments against fishermen; Structuring local institutions; Providing quotas for fisheries and aquaculture, and determination of customary rights.Keywords: sustainable, holistic, fishermen, quotas, customary rights.